Deep Learning Pedagogy through STEM Coding for Elementary Teachers: Strengthening Computational Thinking and Curriculum Implementation Readiness - Hermita, Neni; Barokah, Rifqa Gusmida Syahrun; Putra, M. Jaya Adi; Suroyo, Suroyo; Asiah, Nur (Kreasi: Jurnal Inovasi dan Pengabdian kepada Masyarakat, 2025)
Abstract This community service programme applied Deep Learning Pedagogy through STEM Coding to strengthen computational thinking (CT) and curriculum implementation readiness among elementary teachers in Bengkalis Regency. A total of 50 teachers from 22 schools participated in a staged instructional sequence, beginning with conceptual reinforcement of CT and STEM in primary science, followed by unplugged coding demonstrations, plug-in coding practice using Scratch for Arduino, and the production of teacher outputs in the form of STEM-coding lesson plans (RPP) and microteaching rehearsals. Evaluation included a CT post-test and assessment of these teacher outputs. The average CT post-test score was 79.3, with 82% reaching mastery (≥70). Eight RPPs were produced, and six met ready to implement status based on objective alignment, activity coherence, classroom feasibility, and formative assessment criteria. The main constraints were uneven digital facilities and variation in articulating CT as observable learner behaviour. This programme provides an initial foothold for gradual scaling and aligns with SDG 4, Asta Cita, and the Eight Graduate Profile Dimensions.